'Give Me 5 Foundation': A Plastic Surgery Charity Mission Helping to Enhance the Surgical Management of Limb Deformities in Rural India. Issue 3 (5th December 2018) - Wood, Benjamin; Chilgar, Ram M.; Chen, Hung-Chi; Nicoli, Fabio
Aim: A third of the world's disease burden remains amenable to surgical intervention with 5 billion people still lacking access to safe surgery and anaesthesia. Plastic Surgery has the potential to play a key role in enhancing access to safe and effective surgical care. Give Me Five is a no-profit organisation aiming to improve the surgical management of limb deformities in countries with limited resources. Methods: Based in Shirdi Hospital, Maharasthtra, India, a team of worldwide plastic surgeons worked in tandem with local healthcare staff to improve the form and function of patients with limb deformities. A diagonal approach was utilised to ensure sustainability with consideration of all public health, pre-operative, peri-operative and post -operative manners addressed. Results: Eighty Eight (88) patients were treated over 4 days. The majority (55) were male with an average age of 24 years. 36% of cases involved release of post burn skin contractures with the remaining procedures including microsurgical reconstruction of traumatic brachial plexus injuries, lymph node transfer for lower limb lymphoedema secondary to filariasis as well as syndactyly reconstruction. At 6 months follow up we have had no complications to date with an average hospital stay of 2 days. Conclusion: Impairment of the limb secondary to trauma, infection or congenital deformity can have a major impact on a patient's physical and psychological health thus impacting daily function. Give Me 5 Foundation is a charity with an aim of improving the surgical burden of disease to the limb in developing countries in a sustainable manner.